Distribution and Habitat Karakteristics of Shrimp Juvenile in Segara Anakan Lagoon - Sri Endah Purnamaningtyas; Didik Wahju Hendro Tjahjo (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
Shrimp is a wealth of fishery resources are abundant and has a high economic value in Laguna Segara lagoon. So the existence and habitat of life from larvae to adult need attention to maintain the survival of shrimp. Therefore, the purpose of this research is to know the distribution of abundance and characteristics of shrimp juvenile habitat in Segara Anakan lagoon. Sampling is done 3 times (June, August and October 2013), with 9 stations Observation station. The results showed that the abundance of shrimp based on the amount in Segara Anakan lagoon was dominated by Metapenaeus elegans (205-8723 ind./1000 m2), whereas the abundance of M. ensis, F merguensis, P. semisulcatus and P. monodon relatively low had the same habitat , ie waters with high fertility and relatively low salinity, relatively high pH. Found in Motean observation station, Muara Dua, Kleces and Majingklak. Harpiosquilla annandalei (0-330 ind/1000 m2), P. monodon (0-238 ind/1000 m2), and Acetes sp (0.1-5.196 ind/1000 m2) sounded a lot of water habitat that contain BOT and high zooplankton abundance. Thus the shrimp Harpiosquilla annandalei, P. monodon, and Acetes sp are found in Tritih observation stations, and are quite commonly found in Kleces observation stations. Keywords: abundance, habitat preferences, juvenile shrimp, Segara Anakan Lagoon